2013
DOI: 10.1128/aac.02132-12
|View full text |Cite
|
Sign up to set email alerts
|

N -Chloramines, a Promising Class of Well-Tolerated Topical Anti-Infectives

Abstract: Antibiotic resistance is a growing public health crisis. To address the development of bacterial resistance, the use of antibiotics has to be minimized for nonsystemic applications in humans, as well as in animals and plants. Possible substitutes with low potential for developing resistance are active chlorine compounds that have been in clinical use for over 180 years. These agents are characterized by pronounced differences in their chlorinating and/or oxidizing activity, with hypochlorous acid (HOCl) as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 57 publications
4
86
0
Order By: Relevance
“…NCT completely eradicated the biofilm in our study, so it can be concluded that it kills bacteria independently of protein production, cell cycle, or proliferation. This is in accordance with its oxidative mechanism of action (5,21) and with its efficacy in treatment of infections of different body sites in humans (for a review, see reference 5). For instance, successful application was demonstrated in purulently coated crural ulcerations and in external otitis in humans (22,23).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…NCT completely eradicated the biofilm in our study, so it can be concluded that it kills bacteria independently of protein production, cell cycle, or proliferation. This is in accordance with its oxidative mechanism of action (5,21) and with its efficacy in treatment of infections of different body sites in humans (for a review, see reference 5). For instance, successful application was demonstrated in purulently coated crural ulcerations and in external otitis in humans (22,23).…”
Section: Discussionsupporting
confidence: 71%
“…However, the mild activity and high tolerability of N-chloro amino acids, particularly NCT, enable application of high concentrations to human tissue, which warrants a sufficient reserve of oxidation capacity despite some reduction (20). This can be of advantage compared with highly reactive oxidants that cause side effects at higher dosages (21). Accordingly, NCT was shown to be effective in topical therapy of infections where biofilms play a role, for instance, purulently coated crural ulcerations and external otitis in humans (22,23) and joint infections in mice (7).…”
Section: Discussionmentioning
confidence: 99%
“…As a representative of the active chlorine compounds, NCT exerts broad-spectrum microbicidal activity against all kinds of pathogens (11,12), which is typical for this class of antiseptics. Due to its low reactivity, which is the reason for its good tolerability in sensitive body regions (12), its killing activity against microorganisms is slower than that with highly reactive compounds, like hypochlorous acid (11,34).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its low reactivity, which is the reason for its good tolerability in sensitive body regions (12), its killing activity against microorganisms is slower than that with highly reactive compounds, like hypochlorous acid (11,34). In previous studies (20,21,35), killing of different Candida species and molds needed incubation times of one or only few hours, and in the present study, that against Scedosporium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation